Characterization of Fluorescent Dissolved Organic Matter in an Affected Pollution Raw Water Source using an Excitation-Emission Matrix and PARAFAC: 10.32526/ennrj/19/2021008 - Sururi, Mohamad Rangga; Dirgawati, Mila; Roosmini, Dwina; Notodarmodjo, Suprihanto (Environment and Natural Resources Journal, 2021)
Cikapundung River is the main raw water source for 2-millions inhabitants of Bandung city but has been severely deteriorated due to organic pollution such as cattle manure, domestic, and agriculture wastes. Dissolved Organic Matter (DOM) in raw water can influence the process of water treatment. This study characterized and identified the origins of fluorescent DOM (FDOM) in Cikapundung River. Raw water samples were collected from intake outlets during dry and rainy seasons and analyzed using Fluorescence Excitation Emission Matrix spectroscopy combined with parallel factor (PARAFAC). FDOM origins were identified by Fluorescence-Index (FI) while autochthonous process contribution in water body was determined by Biological-Index (BIX). Chromophoric DOM as UV absorbance at 254 nm (A254) and Chemical Oxygen Demand (COD) were also measured. The FI were 1.82 (dry season) and 1.77 (rainy season), and the BIX were 0.92 (dry season) and 0.65 (rainy season). PARAFAC identified three compounds: water contaminant-like (C1), humic-like (C2) and tryptophan-like (C3) compounds. C2 was predominantly present in the rainy season with a C3/C2 ratio of 0.33. In the dry season, C3 increased substantially with a C3/C2 of 1.60. Strong correlation between C1 and C3 (R=0.86) was evidence that contaminant-like and tryptophan-like compounds were from the same anthropogenic sources. Strong correlation with A254 may indicate these identified compounds are aromatics.